Gut and genital tract microbiomes: Dysbiosis and link to gynecological disorders - Elkafas, Hoda; Walls, Melinique; Al-Hendy, Ayman; Ismail, Nahed (Frontiers in Cellular and Infection Microbiology, 2022)
Every year, millions of women are affected by genital tract disorders, such as bacterial vaginosis (BV), endometrial cancer, polycystic ovary syndrome (PCOS), endometriosis, and uterine fibroids (UFs). These disorders pose a significant economic burden on healthcare systems and have serious implications for health and fertility outcomes. This review explores the relationships between gut, vaginal, and uterine dysbiosis and the pathogenesis of various diseases of the female genital tract. In recent years, reproductive health clinicians and scientists have focused on the microbiome to investigate its role in the pathogenesis and prevention of such diseases. Recent studies of the gut, vaginal, and uterine microbiomes have identified patterns in bacterial composition and changes across individuals’ lives associated with specific healthy and diseased states, particularly regarding the effects of the estrogen–gut microbiome axis on estrogen-driven disorders (such as endometrial cancer, endometriosis, and UFs) and disorders associated with estrogen deficiency (such as PCOS). Furthermore, this review discusses the contribution of vitamin D deficiency to gut dysbiosis and altered estrogen metabolism as well as how these changes play key roles in the pathogenesis of UFs. More research on the microbiome influences on reproductive health and fertility is vital.